Formulating Well-Written Clinical Practice Questions and Research Questions - Natalie Bermudez (Library & Knowledge Services and Nursing & Health Sciences Research Departments, 2021)
Implementation of evidence-based practices is an expectation in healthcare and nursing, requiring knowledge and understanding of evidence-based practice (EBP) and research. Recent evidence shows that nurses' lack of knowledge contributes to nurses' lack of participation in EBP and research and their ability to differentiate between the two posing challenges with writing clinical questions and research questions. The purpose of this article is to provide foundational education on the differences, similarities, and relationship between EBP and research, and provide guidance for writing clinical practice and research questions.